Evaluation of in situ simulated dredging to reduce internal nitrogen flux across the sediment-water interface in Lake Taihu, China. (July 2016) - Yu, Juhua; Fan, Chengxin; Zhong, Jicheng; Zhang, Yinlong; Wang, Changhui; Zhang, Lei
Abstract: Sediment dredging is considered an effective restoration method to reduce internal loading of nitrogen (N) and phosphorus (P) in eutrophic lakes. However, the effect of dredging on N release from sediments to overlying water is not well understood. In this study, N exchange and regeneration across the sediment-water interface (SWI) were investigated based on a one-year simulated dredging study in Lake Taihu, China. The results showed low concentrations of inorganic N in pore water with low mobilization from the sediments after dredging. The calculated fluxes of NO3 − -N from post-dredged sediments to overlying water significantly increased by 58% ( p < 0.01), while those of NH4 + -N dramatically decreased by 78.2% after dredging ( p < 0.01). N fractionation tests demonstrated that the contents and lability of N generally declined in post-dredged sediments. Further high-throughput sequencing analysis indicated that relative abundance of the bacterial communities decreased, notably by 30% (compared with undredged sediments). The estimated abundance of Nitrospira enhanced, although the relative abundance of Thiobacillus, Sterolibacterium, Denitratisoma, Hyphomicrobium, Anaeromyxobacter and Caldithrix generally declined after dredging. Therefore, dredging reduced N mobilization from the sediments, which primarily due to decreases in N mobility, in organic matter (OM) mineralization potential and in the bacterial abundance of post-dredged sediments. Overall, to minimize internal N pollution, dredging is capable of effectively reducing N release from sediments. In addition, the negative side effect of dredging on removal of NO3 − -N and NO2 − -N from aquatic ecosystems should be paid much more attention in future. Graphical abstract: Highlights: Evaluation of dredging to control N release based on a one-year simulation study. Dredging removed sediments with high concentration of inorganic N in pore water. Dredging decreased the contents and mobility of sediment N. Dredging reduced the relative abundance of bacterial communities in sediments. Dredging lead to a condition that probably weaken removal of NOx − from lake ecosystem. Abstract : Dredging is capable of effectively reducing N release from sediments, while probably weakening the removal of NOx − -N (nitrate-plus-nitrite) from aquatic ecosystems.